DAMPAK INDUSTRI PT. GLOBAL COCONUT TERHADAP MASYARAKAT DI DESA RADEY, KECAMATAN TENGA, KABUPATEN MINAHASA SELATAN - Andreas ., Rasu; Noortje Marsellanie Benu; Elsje Pauline Manginsela (AGRI-SOSIOEKONOMI, 2017)
The purpose of this study to determine the impact of the presence of Coconut Flour Industry (PT. Global Coconut) to the community in the Radey Village. This research was carried out on members of the village community Radey as respondents. Total respondents 32 people consisting of workers in the industry (25 persons), who did not work in the industry that ordinary members of community (5 persons) and community leaders (2 persons). The study lasted for 3 months from September to November 2016. The sample selection using snowballing method. Types of data collected in this study are primary and secondary data. Primary data is data obtained by direct interview to the respondents. Secondary data is obtained from the Village Office. The data collected concerning Identity Respondents, namely: (1) Name of Respondent, (2) age, expressed in units of years, (3) Level of education, measured by educational level already attained (elementary, junior high, high school, diploma, and University). Data regarding positive or negative impact of the presence of Industry on the community in the village of Radey regarding: (1) Income received before and after working in the company, (2) employment opportunities, (3) business opportunities. The analytical method used in this research is descriptive analysis method qualitative and quantitative modest presented in tabular form. The results of this research showed that the presence of PT Global Agro-Industry Plant in the Radey Village has gave positive and negative impacts for rural communities in the form of increases in income, employment and business opportunity, the new procurement of agricultural roads better and their support for the national celebration activities in the village. The negative impact of such a foul odor had happened only when the management of the rest of the selection in the form of broken coconut and waste production is not done well.Keywords: impact, agro-industry, community, village Radey, South Minahasa District